2011
DOI: 10.1128/aac.00506-10
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Paromomycin on Ribosomes of Leishmania mexicana and Mammalian Cells

Abstract: Paromomycin, an aminoglycoside antibiotic having low mammalian cell toxicity, is one of the drugs currently used in the chemotherapy of cutaneous and visceral leishmaniasis. In order to understand the mode of action of this antibiotic at the molecular level, we have investigated the effects of paromomycin on protein synthesis in Leishmania and its mammalian hosts. We were able to demonstrate that in vivo protein synthesis in the promastigote stage of the parasite and its proliferation rate are markedly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
2
38
0
2
Order By: Relevance
“…The LC 50 values obtained for the 6′-OH AGs (Paromomycin and G418) were in the μM range, and showed good agreement with previous published values for these compounds (18,35,36). The obtained LC 50 values for the 6′-NH 2 derivatives (Neomycin and Gentamicin) were higher than those obtained for the 6′-OH derivatives, and are also in good agreement with previously reported work demonstrating the lower potency of Neomycin B, compared with Paromomycin, for treatment of leishmaniasis (18). These results are also correlated well with the fact that 6′-NH 2 derivatives are less effective against AG resistant bacterial strains containing an A1408G substitution (30).…”
Section: In Vitro Inhibition Of Leishmania Donovani and Leishmania Majorsupporting
confidence: 75%
See 2 more Smart Citations
“…The LC 50 values obtained for the 6′-OH AGs (Paromomycin and G418) were in the μM range, and showed good agreement with previous published values for these compounds (18,35,36). The obtained LC 50 values for the 6′-NH 2 derivatives (Neomycin and Gentamicin) were higher than those obtained for the 6′-OH derivatives, and are also in good agreement with previously reported work demonstrating the lower potency of Neomycin B, compared with Paromomycin, for treatment of leishmaniasis (18). These results are also correlated well with the fact that 6′-NH 2 derivatives are less effective against AG resistant bacterial strains containing an A1408G substitution (30).…”
Section: In Vitro Inhibition Of Leishmania Donovani and Leishmania Majorsupporting
confidence: 75%
“…Although no direct evidence is currently available showing that G418 induces miscoding by leishmanial ribosomes, G418 has long been marked as a potent miscoding agent in eukaryotes (38). In addition, a recent work has demonstrated the ability of a structurally related derivative, Paromomycin, to induce miscoding in Leishmania (18). Our modeling data with Paromomycin indeed indicate that the two compounds share a rather great similarity in their binding mechanisms and both might cause the induction of an ON-state conformation upon binding (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This antibiotic has shown strong anti-leishmania activity when used alone or in combination with other drugs [75]. In a recent work, advances on the molecular basis for the differential effect of paromomycin on Leishmania have been reported [4]. In this work it was demonstrated that paromomycin selectively inhibits the rate of in vitro protein synthesis by trypanosomatid ribosomes, comparing to mammalian extracts.…”
Section: Selective Inhibition Of Trypanosomatid Ribosomes By Paromomycinmentioning
confidence: 75%
“…Interestingly, this region forms the decoding center, and is also the action site of aminoglycoside antibiotics. Moreover, differences in this region have shown to be responsible for the higher susceptibility of trypanosomatid ribosomes to the aminoglycoside paromomycin [4], as will be discussed below.…”
Section: Introductionmentioning
confidence: 99%